Potassium fertilization for fresh market potato production in tropical soils - Job, André L.G. [UNESP]; Soratto, Rogério P. [UNESP]; Fernandes, Adalton M. [UNESP]; Assunção, Natália S. [UNESP]; Fernandes, Fabiana M. [UNESP]; Yagi, Renato (Wiley, 2019)
Potassium (K) is the most taken up and removed nutrient by potato (Solanum tuberosum L.), and has a great influence on tuber yield and quality. This study was performed to evaluate the effects of three rates (100, 200, and 400 kg K2O ha–1) and two timings of application of K (single application at planting furrow and split application of 50% at planting furrow plus 50% at hilling), as potassium chloride, as well as a control (without K application) on the plant nutrition and tuber yield and quality of potato ‘Agata’ grown in tropical clay soils. The split application of K fertilizer had little influence on plant nutrition and tuber yield and quality. The influence of K fertilization on increasing K and reducing Ca and Mg concentrations in the leaf was more significant in soil with low exchangeable K. In this soil, the maximum tuber yield (33.6 Mg ha–1; 107% higher than the control) was obtained with an estimated rate of 325 kg K2O ha–1, while in the soils with medium and high exchangeable K, the tuber yield was increased between 22 and 34% and only up to a rate of 200 kg K2O ha–1. The critical leaf K concentration to reach 95% of the maximum yield was 29.3 g K kg–1, but there was an extreme increase in the tuber yield even with K rates that provided leaf K concentrations above this limit. Potassium fertilization increased the firmness and reduced soluble solids and protein in tubers.